MOLECULAR GENETIC CHARACTERISTICS OF THE RABIES VIRUS, PATHOGENESIS AND ACHIEVEMENTS IN THE DIAGNOSIS AND DEVELOPMENT OF CONTROL TOOLS (Experimental biology, 2023)
Rabies occurs worldwide in a variety of reservoir animals and is known to be the most deadly viral infection with nearly 100% fatality after symptom onset. Rabies is still endemic in more than 150 countries and territories, resulting in an annual economic loss of about US$8.6 billion and continues to kill an estimated 40,000–70,000 people a year, approximately 40% of which are children. The danger of rabies lies in the fact that no effective treatment has yet been found and the disease is usually fatal. Most of these deaths occur in countries with limited resources, where a lack of infrastructure hinders early warning and post-exposure prophylaxis, and the ubiquity of domestic and wild animal hosts makes eradication unlikely. The problem of rabies in Kazakhstan remains unresolved, natural foci of the disease are constantly recorded, which requires more effective measures to prevent and combat rabies. This review focuses on issues related to the molecular genetic characterization of the rabies virus, pathogenesis, and the spread of rabies in the world and Kazakhstan. The results of a study on the development of anti-rabies drugs and diagnostic methods are described in detail.
Keywords: rabies virus, glycoprotein G, anti-rabies immunoglobulin.